2019
DOI: 10.1108/ijhcqa-05-2018-0106
|View full text |Cite
|
Sign up to set email alerts
|

Can Bahraini patients accept e-health systems?

Abstract: Purpose The purpose of this paper is to examine whether Bahraini individuals accept e-health system and the prominent factors affecting e-health system adoption in Bahrain. Design/methodology/approach The authors adopted a quantitative and qualitative approach, i.e., a self-administered questionnaire, unstructured and a semi-structured interview, which were used to collect the data. A questionnaire was distributed to Bahraini residents selected randomly. The framework was based on the technology acceptance m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
0
10
0
6
Order By: Relevance
“…Novel information and communication technologies (ICTs) are transforming the patient experience in healthcare systems (Scott Kruse et al , 2018; Harst et al , 2019; Zolait et al , 2019). Telehealth, eHealth and telemedicine are trends related to these emerging technologies (Harst et al , 2019; Verma et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Novel information and communication technologies (ICTs) are transforming the patient experience in healthcare systems (Scott Kruse et al , 2018; Harst et al , 2019; Zolait et al , 2019). Telehealth, eHealth and telemedicine are trends related to these emerging technologies (Harst et al , 2019; Verma et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Patient acceptance is a core research topic and some researchers have also investigated their role in telemedicine adoption (e.g. Zolait et al , 2019). Studies have prioritized elderly people (Etemad-Sajadi and Gomes Dos Santos, 2019; Tsai et al , 2019; Zhou et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zolait et al [41] examined the acceptance of the e-health system among users in Bahrain, as well as the factors that impacted its adoption. They used a mixed approach, along with the technology acceptance model and the theory of reasoned action framework [42,33].…”
Section: Health Concerns In Bahrainmentioning
confidence: 99%
“…Exploring health-related or medical information is among the most common online activities undertaken by consumers of healthcare services (Zolait, Radhi, Alhowaishi, Sundram, & Aldoseri, 2019). Pew Internet & American Life Project conducted surveys and concluded that about 75 to 80 internet users out of 100 in America have used the internet to search for health-related information, particularly by 55 percent of the household users who have broadband internet access (D. Kumar & Bansal, 2015).…”
Section: Introductionmentioning
confidence: 99%